Low appendicular muscle mass is correlated with femoral neck bone mineral density loss in postmenopausal women - Orsatti, Fabio L.; Nahás, Eliana Aguiar Petri [UNESP]; Nahas-Neto, Jorge [UNESP]; Orsatti, Claudio L. [UNESP]; Marocolo, Moacir; Barbosa-Neto, Octavio; da Mota, Gustavo R. (Biomed Central Ltd., 2011)
Background: After menopause, rapid bone mass loss occurs in response to hypoestrogenism. Several studies suggest that muscle mass and bone mineral density (BMD) are positively associated in postmenopausal women. Therefore, it may be assumed that postmenopausal low appendicular muscle mass (aMM) can increase BMD loss in a short period of time.Objective: The purpose of this study was to assess relationship of aMM with femoral neck BMD in postmenopausal women.Methods: Prospective, controlled clinical Trial including 64 women aged 45-70 years, who had not had their last menstruation for at least one year. Subjects were divided into two groups: low aMM (n = 32), and normal aMM (n-32). Femoral neck BMD and muscle mass were measured by DXA at baseline and after twelve months. Pairwise and independent t tests were used for data analysis.Results: Baseline weight, BMI and muscle mass (total and appendicular) significantly differ between groups (p < 0.05). After twelve months, femoral neck BMD was significantly lower in the group with low aMM, whereas no significant difference was observed in the group with normal aMM (p < 0.05).Conclusion: In postmenopausal women, low appendicular muscle mass is associated negatively with femoral neck BMD in a short period of time.
Keywords: sarcopenia; osteoporosis; menopause; body composition; DXA